178k views
10 votes
Help me and please show your work 6(x-2) = 3(x-8)

User Morton
by
5.7k points

2 Answers

8 votes
Answer :
x =-4


Step-by-step explanation :
6(x-2) =3(x-8)
6x-12 =3x -24
6x -3x = -24 +12
3x = -12
x = -12/3
x =-4
User Paul Alan Taylor
by
5.8k points
8 votes

Answer:

-4

solution of this question = 6(x-2) = 3(x-8)

6x - 12 = 3x -24

6x- 3x = -24+ 12

3x = - 12

x = -12/3

x = -4

hope it helps

User Andreas Veithen
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.